ACEH GOVERNMENT POLICY ANALYSIS ON POTENTIAL OF THE NATURAL RESOURCES EXPORT MARKET - azhar, Iqlima; Fajriah, Agustina Nurul (Jurnal Transformasi Administrasi, 2024)
With the establishment of regional autonomy, each area must be able to identify and recognize the potential and superior or basic sectors that it owns at both the provincial and village levels. Aceh, as one of the most strategically positioned provinces in Indonesia, has long served as a conduit for trade and cultural flow connecting Timor and the West. Because to geopolitical situations, Aceh Province now has the possibility to boost its economic potential through encouraging company development. Focus of this research is to assess the export potential of natural resource goods in Aceh Province, determine the degree of production of these natural resources, and analyze natural resources with export potential. The Location Quotient (LQ) is used as an analytical tool to identify natural resources with the potential to be exported. The East Aceh District has a continual superior LQ value (LQ> 1) from 2018 to 2022, according to the results of the Location Qoutient (LQ) research. Langsa City and North Aceh Regency are classified as non-base sectors (LQ<1).